Pengaruh Lingkungan Keluarga terhadap Keterampilan Berkomunikasi Efektif Anak Usia Dini - Nurul Aini MM Sodik; Nahara R.Yamudu; Tria Oktaviani Jannati; Farah Anggraini; Tiara Avrianti Pilo (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to analyze the impact of the family environment on effective communication skills in early childhood. The family environment, as the first and foremost setting, plays a crucial role in shaping children's communication skills, both through parenting styles, verbal interactions, and the emotional atmosphere within the home. The research method used is a qualitative approach with descriptive analysis techniques, which focuses on describing phenomena based on data obtained through observation and literature review. The results show that children who grow up in a communicative, supportive, and responsive family environment tend to have better communication skills, such as the ability to express opinions, listen well, and interact effectively with others. Conversely, a less harmonious family environment with minimal interaction can hinder the development of children's communication skills. Thus, it can be concluded that the family environment has a significant influence on the effective communication skills of early childhood, so the role of parents is essential in creating a positive and constructive communication atmosphere within the family.